Pengaruh lama pengeringan ampas tahu menggunakan oven dryer terhadap mutu tempe ampas tahu [The effect of drying time of tofu dregs using an oven dryer on the quality of its tempeh] - Yarfaryh, Uswatun Hasanah; Handayani, Baiq Rien; Ariyana, Mutia Devi; Perdhana, Firman Fajar; Namira, Afrisha Sekar (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2023)
Tofu dregs tempeh is tempeh made from by-products of tofu processing. Tofu dregs tempeh contains high water content to exceed the SNI standard. The objective of this research was to determine the effect and the best result of drying time using an oven dryer at 60oC on the quality of tofu dregs tempeh. The method used in this research was a Completely Randomized Design (CRD) with seven treatments drying times 0, 15, 30, 45, 60, 7, and 90 minutes at 60oC. Significant difference data were tested for parameters of chemical quality (water content and water activity), and microbial quality (total microbial, mold mass, and mycelium area). A drying time of 60 minutes is recommended as the best treatment to produce tofu dregs tempeh with the following characteristic of 61.77% water content which has met the requirement of SNI No. 3144:2015; 0.82 water activity (Aw); 5.89 log CFU/g total microbial; 1.72% mold mass and; 30.66% mycelium area.